Insomnia and Fatigue Symptom Trajectories in Breast Cancer: A Longitudinal Cohort Study. Issue 6 (2nd November 2021) - Bean, Helena R.; Diggens, Justine; Ftanou, Maria; Weihs, Karen L.; Stanton, Annette L.; Wiley, Joshua F.
ABSTRACT: Objective : Insomnia and fatigue are common, although not inevitable, during breast cancer. This study is one of the first aiming to describe distinct trajectory classes of insomnia and fatigue symptoms, and their correlates, from diagnosis through treatment. Methods : This longitudinal cohort study was conducted at a comprehensive cancer center and community oncology practices. Participants ( N = 460) were women diagnosed with any stage of breast cancer in the previous 4 months. Primary outcomes for this ancillary study of the existing cohort were self-reported insomnia and fatigue symptoms assessed repeatedly across 12 months. Results : Four distinct classes of insomnia symptoms emerged: persistently very high, clinically elevated symptoms (13.7%); high, clinically elevated symptoms (65.9%); stable low (17.2%) or very low (2.6%) symptoms. Five fatigue symptom classes included high, increasing fatigue (9.6%), two recovery classes starting at high (26.3%), or moderate (18.0%) severity at diagnosis, stable low (33.3%) or very low (12.2%) classes. In multivariate analyses, higher depressive symptoms, anxiety, and chronic life stress were associated with being in the very high insomnia class versus the low symptom class. Oncologic factors were not associated with insomnia class membership. Receiving chemotherapy was linked significantly to high and recovery fatigue symptom classes versus the low class. Higher chronic life stress was associated with more persistent fatigue symptoms. Conclusions : Distinct classes of insomnia and fatigue symptoms were evident; 79.6% of the women had clinically elevated, persistent insomnia symptoms, 53.9% had elevated fatigue. A substantial minority evidenced low symptoms, suggesting targeted or stepped-care approaches to symptom management.